Interaction of straw amendment and soil NO3− content controls fungal denitrification and denitrification product stoichiometry in a sandy soil. (November 2018) - Senbayram, Mehmet; Well, Reinhard; Bol, Roland; Chadwick, David R.; Jones, David L.; Wu, Di
Abstract: The return of agricultural crop residues are vital to maintain or even enhance soil fertility. However, the influence of application rate of crop residues on denitrification and its related gaseous N emissions is not fully understood. We conducted a fully robotized continuous flow incubation experiment using a Helium/Oxygen atmosphere over 30 days to examine the effect of maize straw application rate on: i) the rate of denitrification, ii) denitrification product stoichiometry N2 O/(N2 O+N2 ), and iii) the contribution of fungal denitrification to N2 O fluxes. Five treatments were established using sieved, repacked sandy textured soil; i) non-amended control, ii) nitrate only, iii) low rate of straw + nitrate, iv) medium rate of straw + nitrate, and iv) high rate of straw + nitrate (n = 3). We simultaneously measured NO, N2 O as well as direct N2 emissions and used the N2 O 15 N site preference signatures of soil-emitted N2 O to distinguish N2 O production from fungal and bacterial denitrification. Uniquely, soil NO3 − measurements were also made throughout the incubation. Emissions of N2 O during the initial phase of the experiment (0–13 days) increased almost linearly with increasing rate of straw incorporation and with (almost) no N2 production. However, the rate of straw amendment was negatively correlated with N2 O, but positively correlated with N2 fluxes later in the experimental period (13–30 days). Soil NO3 − content, in all treatments, was identified as the main factor responsible for the shift from N2 O production to N2 O reduction. Straw amendment immediately lowered the proportion of N2 O from bacterial denitrification, thus implying that more of the N2 O emitted was derived from fungi (18 ± 0.7% in control and up to 40 ± 3.0% in high straw treatments during the first 13 days). However, after day 15 when soil NO3 − content decreased to <40 mg NO3 − -N kg −1 soil, the N2 O 15 N site preference values of the N2 O produced in the medium straw rate treatment showed a sharp declining trend 15 days after onset of experiment thereby indicating a clear shift towards a more dominant bacterial source of N2 O. Our study singularly highlights the complex interrelationship between soil NO3 − kinetics, crop residue incorporation, fungal denitrification and N2 O/(N2 O + N2 ) ratio. Overall we found that the effect of crop residue applications on soil N2 O and N2 emissions depends mainly on soil NO3 − content, as NO3 − was the primary regulator of the N2 O/(N2 O + N2 ) product ratio of denitrification. Furthermore, the application of straw residue enhanced fungal denitrification, but only when the soil NO3 − content was sufficient to supply enough electron acceptors to the denitrifiers. Highlights: Straw application rate does not directly affect N2 O/(N2 O+N2 ) ratio. N2 O emission following straw application is controlled by soil NO3 − content. Straw addition increases fungal N2 O.